The Decade 1989-1998 in Spanish Psychology: An Analysis of Research in Developmental and Educational Psychology. - Sánchez-miguel, Emilio; García-sánchez, Jesús-Nicasio (The Spanish Journal of Psychology, 2001)
Sin resumen